Daniel - Rich, Richard; Nest Entertainment, Inc.; Rich Animation Studios (Coppell, TX : Nest Entertainment, 2005)
When Daniel survives being thrown into the lions' den, he proves that God still rules over the affairs of men.
Includes Resource and Activity Book.
Produced and directed by Richard Rich.
"Premium website accessible through DVD-ROM"--Container.
"NEST complete learning system."
DVD ; Dolby digital 2-channel surround sound.
In English with optional Spanish language track and optional English or Spanish subtitles.
Keywords: Daniel -- (Biblical figure) -- Juvenile films; Bible stories; Animated films; Children's films